2006
DOI: 10.3151/jact.4.99
|View full text |Cite
|
Sign up to set email alerts
|

Study on Impact Response of Reactive Powder Concrete Beam and Its Analytical Model

Abstract: The aim of this study was to experimentally examine the impact response of a RPC (Reactive Powder Concrete) beam and develop an analytical model to represent its impact response. Thus, a drop hammer impact test was performed to investigate the influence of drop height of the hammer on the impact response of the RPC beam. Subsequently, a static flexural loading test was conducted to find out the residual load carrying capacity of the RPC beam after impact loading. In the impact analysis, the two degrees of free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 2 publications
0
44
0
5
Order By: Relevance
“…A higher ultimate load capacity was also obtained for the beams under impact loading, compared to those under quasi-static loading, and the residual load capacity after impact damage improved by including 2 % steel fibers and using the longer steel fibers. Fujikake et al (2006a) and Yoo et al (2015a) successfully predicted the mid-span deflection versus the time response of structural UHPFRC beams by using the sectional analysis and single-(or multi-) degree-of-freedom model. Improved mechanical compressive and tensile strengths according to the strain-rate were considered in the analysis by using the equations for the dynamic increase factor (DIF) of the UHPFRC, as suggested by Fujikake et al (2006bFujikake et al ( , 2008.…”
Section: Torsional Behavior Of Structural Uhpfrc Beams and Girdersmentioning
confidence: 99%
See 4 more Smart Citations
“…A higher ultimate load capacity was also obtained for the beams under impact loading, compared to those under quasi-static loading, and the residual load capacity after impact damage improved by including 2 % steel fibers and using the longer steel fibers. Fujikake et al (2006a) and Yoo et al (2015a) successfully predicted the mid-span deflection versus the time response of structural UHPFRC beams by using the sectional analysis and single-(or multi-) degree-of-freedom model. Improved mechanical compressive and tensile strengths according to the strain-rate were considered in the analysis by using the equations for the dynamic increase factor (DIF) of the UHPFRC, as suggested by Fujikake et al (2006bFujikake et al ( , 2008.…”
Section: Torsional Behavior Of Structural Uhpfrc Beams and Girdersmentioning
confidence: 99%
“…The initial stiffness in the UHPFRC beams was insignificantly affected by the impact damage because of the excellent fiber bridging capacities after matrix cracking, and the residual load-deflection (or moment-curvature) curves, shifted based on the maximum deflection by impact, exhibited quite similar behaviors with those of the virgin specimens without impact damage. Hence, Fujikake et al (2006a) mentioned that the maximum deflection response can be used as the most rational index for estimating the overall flexural damage of reinforced UHPFRC beams. Yoo et al (2015a) reported that better impact resistance, i.e., lower maximum and residual deflections and higher deflection recovery, was obtained by increasing the amount of longitudinal steel rebars, and the maximum and residual deflections of reinforced UHPFRC beams decreased significantly by adding 2 % (by volume) of steel fibers, leading to a change in the damage level from severe to moderate, whereas slight decreases in the maximum and residual deflections were found by increasing the fiber length at identical volume fractions (Yoo et al 2015c).…”
Section: Torsional Behavior Of Structural Uhpfrc Beams and Girdersmentioning
confidence: 99%
See 3 more Smart Citations